Aerodynamic performance evaluation of steel-UHPC composite deck cable-stayed bridges with VIV countermeasures. (April 2023) - Yang, Yongxin; Zhu, Jinbo; Zhou, Rui; Ge, Yaojun; Xu, Haojun; Zhang, Lihai
Abstract: The steel-ultrahigh performance concrete (UHPC) composite girder makes the bridge deck thinner and more streamlined, but their effects on the aerodynamic performance of cable-stayed bridges are unclear. With the developed equivalent girder analysis method, the overall aerodynamic performance ( e.g. vortex-induced vibration (VIV), flutter, aerostatic and buffeting performance) of a steel-UHPC composite girder cable-stayed bridge with various VIV countermeasures are systematically evaluated by conducting a series of wind tunnel tests and numerical calculation. The results show that the developed equivalent girder analysis method could simplify the sectional model design of the composite girder for wind tunnel tests. Only the guide vane removal cannot suppress the torsional VIV responses among various combinations of guide vanes removal, while the two VIV countermeasures ( e.g. the removal of outside railing cornerstones, the removal of four guide vanes and outside railing cornerstones) could reach about 76% and 72% of the torsional VIV amplitudes, respectively. Although two VIV countermeasures could slightly reduce the critical flutter wind speed, their torsional divergence critical wind speeds are much larger than the limited design requirement. Moreover, the removal of four guide vanes and outside railing cornerstones has the capacity of improving the aeroelastic and buffeting performance of the bridge, as the best overall aerodynamic performance. Highlights: An equivalent girder analysis method of steel-UHPC composite girders was developed to simplify the wind tunnel tests design. Overall aerodynamic performance of a composite girder cable-stayed bridge with various VIV countermeasures are evaluated. Among fifteen ancillary facilities dislodge, the dislodge of outside railing cornerstones and four guide vanes are two effective VIV countermeasures. The removal of outside railing cornerstones and four guide vanes are two effective VIV countermeasures among fifteen cases. Two effective VIV countermeasures have the capacity of improving the aeroelastic and buffeting performance of the bridge.